Penanaman Seribu Pohon Sebagai Upaya Mencegah Banjir dan Tanah Longsor di Desa Eyat Mayang, Lembar, Nusa Tenggara Barat - Prapti Sedijani; Miko Eniarti; Nurwidianti; Siska Yulia Hermana; Jumriani (Jurnal Pengabdian Magister Pendidikan IPA, 2022)
Eyat Mayang is a hilly Village where landslides can occur during heavy rains. The rainfall makes the dike unable to accommodate the overflow from the river. This condition is exacerbated by the unavailability of a Garbage Final Destination (TPA), causing the community to throw their garbage in the river. In addition, silting of the river naturally occurs. Garbage piling and river siltation are the main causes for flooding. Based on data, in 2021 there were 2 floods that resulted in damage to infrastructure, housing, and public facilities, which caused substantial material losses beside the immaterial things. There were 785 families that were impacted by floods in 2021. Therefore, Students of Mataram University (UNRAM) who were conducting Integrated Community Service in the area Period of 2021/2022 carry out programs, one of which was called "Towards a Disaster Response Village" (DESTANA). This service is an effort to prevent the danger of flooding and land sliding in the future by planting a thousand trees at certain points agreed by the leadership, village officials, and the local community. The seedlings planted were provided by the Mataram Environment and Forestry Service, West Nusa Tenggara. This service is carried out in mutual cooperation with Bhabinsa, village officials, and the local community. Activities were conducted in stages in several designated hamlets. The community were very enthusiastic about the program with the hope that this program will be able to reduce or even overcome floodings and landslides. Moreover, we all hope that the Tree Planting Program increases the awareness of the communitiy about protecting the environment. We do hope that the trees will reduce the increase of global warming.